Drought tolerance in three maize cultivars is related to differential osmolyte accumulation, antioxidant defense system, and oxidative damage - Anjum, Shakeel Ahmad; Ashraf, Umair; Tanveer, Mohsin; Khan, Imran; Hussain, Saddam; Zohaib, Ali; Abbas, Farhat; Saleem, Muhammad Farrukh; Wang, Longchang (Frontiers in Plant Science, 2017)
Consequences of drought stress in crop production systems are perhaps more deleterious than other abiotic stresses under changing climatic scenario. Regulations in physio-biochemical responses under drought stress are crafted in to agronomic traits by the plants that can be used as markers for drought stress tolerance from selection and breeding point of view. Present study was conducted to appraise the performance of three different maize hybrids i.e., Dong Dan 80, Wan Dan 13 and Run Nong 35 under well watered, low, moderate and severe drought conditions maintained at 100, 80, 60 and 40% field capacities, respectively. Compared with well-watered, drought stress exhilarated oxidative stress in terms of reactive oxygen species (ROS) production which led to reduced growth and yield formation in all maize hybrids; nevertheless negative effects were more prominent in Run Nong 35. Drought-induced osmolyte accumulation and strong enzymatic and non-enzymatic defense system prevented severe damages in Dong Dan 80. Furthermore, in most of the cases correlations of ROS, omolytes and anti-oxidant defense system were found negative with shoot dry weight (SDW), grain yield (GY) and biological yield (BY) under drought conditions. Overall performance of all maize hybrids under drought stress was recorded as: Dong Dan 80 > Wan Dan 13 > Run Nong 35 with 6.39, 7.35 and 16.55% yield reductions. Consequently, these biochemical traits and differential physiological responses might be helpful to develop drought tolerance genotypes that can withstand against water-deficit conditions with minimum yield losses.